Effect of level of protein in the productive performance of juveniles the tiburoncito Ariopsis seemanni (Orinoquia, 2014)
El tiburoncito (Ariopsis seemanni) a Colombian Pacific fish and in order to meet the zootechnical performance this aspect is important in the future incorporation of the tiburoncito of Colombian marine aquaculture, took place this experiment. We were aimed to evaluate the growth and survival of juveniles of this species, feeding with five commercial diets. Prior to the experiment an adaptation period of 30 days in which the fish were adapted to the laboratory and the consumption of the commercial diet were performed. The statistical design was completely randomized with three replications. We were used plastic tanks with volume of 40 L, 20 juveniles per experimental unit and these were maintained at a salinity of 10%. Fish were fed three times per day at a rate of 6% of biomass per day, for a period of 58 days. Survival rates, increase in weight, growth rate and specific hepatosomatic index were determined. The fish had an initial weight of 3.25 ± 0.26 g. The compositional analysis of commercial diets with protein levels (24, 32, 40, 45 and 48%) had an actual protein level of 28, 37, 45, 50 and 53%. Diets were obtained 45, 50 and 53% are not significantly different (P> 0.05) in the rates of production performance; survival was greater than 75%; the maximum daily increase in weight was 0.06 g / day diet 53% and the minimum was 0.03 g / day diet 28%, representing a difference of 50% between diets. With the 53% protein level diet has an optimum growth and survival close to 75%, and this concentration of protein represent a higher cost per gram of diet. However, the 45% protein diet shows a less weight increase and a 95% survival, and an around 95% survival, this cost effective, because is due to the Increased number of living fish.
Keywords: Ariopsis seemanni; productive performance; nutrition; survival